Utilization and uptake of clinical genetics services in high-income countries: A scoping review. Issue 7 (July 2021) - Dragojlovic, Nick; Kopac, Nicola; Borle, Kennedy; Tandun, Rachel; Salmasi, Shahrzad; Ellis, Ursula; Birch, Patricia; Adam, Shelin; Friedman, Jan M.; Elliott, Alison M.; Lynd, Larry D.
Highlights: System-wide utilization of clinical genetics services in high-income countries is growing rapidly. Most genetic services utilization currently takes place in cancer and prenatal care. Uptake of genetic services varies widely across clinical areas and health systems. Technological advances are a major driver of growth in genetic services utilization. Abstract: Ongoing rapid growth in the need for genetic services has the potential to severely strain the capacity of the clinical genetics workforce to deliver this care. Unfortunately, assessments of the scale of this health policy challenge and potential solutions are hampered by the lack of a consolidated evidence base on the growth in genetic service utilization. To enable health policy research and strategic planning by health systems in this area, we conducted a scoping review of the literature on the utilization and uptake of clinical genetics services in high-income countries published between 2010 and 2018. One-hundred-and-ninety-five unique studies were included in the review. Most focused on cancer (85/195; 44%) and prenatal care (50/195; 26%), which are consistently the two areas with the greatest volume of genetic service utilization in both the United States and other high-income countries. Utilization and uptake rates varied considerably and were influenced by contextual factors including health system characteristics, provider knowledge, and patient preferences. Moreover, growth in genetic service utilization appears to be driven to a significant degree by technological advances and the integration of new tests into clinical care. Our review highlights both the policy challenge posed by the rapid growth in the utilization of genetic services and the variability in this trend across clinical indications and health systems.